2016
DOI: 10.5751/es-08787-210436
|View full text |Cite
|
Sign up to set email alerts
|

Flow and rent-based opportunity costs of water ecosystem service provision in a complex farming system

Abstract: rent-based opportunity costs of water ecosystem service provision in a complex farming system. Ecology and Society 21 (4) ABSTRACT. Unsustainable land uses present many challenges for securing ecosystem service provision. It is also difficult to estimate the cost of a transition to more sustainable land-management practices for individual landholders. The main cost to landholders is the opportunity costs, the income foregone when changing land use for continued or enhanced ecosystem service provision. Thus acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(84 reference statements)
0
3
0
2
Order By: Relevance
“…Although anthropogenic uses can act negatively on the preservationist prism of the PPAs in Scenarios III, Bertini, Fushita and Lima (2015), Platiau et al (2014), and Rendon, Dallimer and Paavola, (2016) found that there is a growing interest in the conservation community in developing strategies to ensure production with conservation of biodiversity and the generation of environmental services in the PPAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although anthropogenic uses can act negatively on the preservationist prism of the PPAs in Scenarios III, Bertini, Fushita and Lima (2015), Platiau et al (2014), and Rendon, Dallimer and Paavola, (2016) found that there is a growing interest in the conservation community in developing strategies to ensure production with conservation of biodiversity and the generation of environmental services in the PPAs.…”
Section: Resultsmentioning
confidence: 99%
“…These areas are covered or not by vegetation and are located alongside water courses, around springs, on steep slopes, and hilltops, among others, and they offer environmental services of the PPAs. Among the main ecosystem services of the PPAs are the preservation of water resources, edaphic and landscape, geological stability, biodiversity flows and the welfare of society (Brazil, 2012a;Coutinho;Freitas;Philippi Júnior, 2014;Rendon;Dallimer;Paavola, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Es necesario contrastar los valores de CO de usos del suelo agrícola encontra-dos, con otras fuentes de información referidas a paisajes agrícolas en zonas en alta montaña andina. En la literatura revisada no se hallaron valores comparativos de CO de usos del suelo agrícola para distintas zonas o regiones, sino para distintos cultivos o métodos en una misma zona de estudio (Wunscher et al, 2011;Rendon et al, 2016), debido a la heterogeneidad de factores que inciden en el cálculo; sin embargo, sí existe una literatura más amplia que compara valores de los pagos acordados para distintos PSA según servicio ambiental o actividades asociadas a la conservación o recuperación de estos (Kosoy, Martínez-Tuna, Muradian & Martínez-Alier, 2007;Wunder, Engel & Pagiola, 2008;Ferraro, 2008;Ojea & Martin-Ortega, 2015;Grima, Singh, Smetschka & Ringhofer, 2016) Teniendo en cuenta lo anterior, se consultó con habitantes de la zona o investigadores que han trabajado en esta área, para tener una idea sobre el precio de arrendamiento y venta de la tierra en la cuenca del lago de Tota. Según lo informado por estos, el valor del arriendo de una hectárea para la siembra en zona apta para el cultivo de cebolla puede oscilar entre los 300 000 pesos/mes y los 2 000 000 pesos/mes.…”
Section: Discussionunclassified
“…sistemas productivos y tipos de cultivos) y las características socioeconómicas de los propietarios o poseedores (p. ej. tenencia de la tierra), entre otros factores (Rendon, Dallimer, & Paavola, 2016).…”
Section: Marco Conceptualunclassified
“…Furthermore, the interplay between agricultural income and environmental considerations has been investigated using diverse methodologies [75][76][77][78][79][80][81][82]. For example, Barbosa et al (2015) estimated that while hydroponic systems in heated greenhouses could yield 11 times more lettuce than traditional soil farming, they required 82 times more energy due to their reliance on electricity [83].…”
Section: Introductionmentioning
confidence: 99%